Apathy, alienation and young people: the political engagement of British millennials - Fox, Stuart (2015)
Conventional wisdom holds that today’s young people, often known as ‘the Millennials’, are a politically alienated generation. Their hostility towards political parties, association with protest movements, and low electoral turnout are all said to indicate their alienation from the processes and institutions of Western democracy. This conventional wisdom stands, however, on shaky ground. Previous research has given too little attention to the definition and measurement of political alienation, and has barely explored its causal relationship with political participation. The use of methods capable of exploring the generational distinctiveness of the Millennials has been limited, as have efforts to outline why the Millennials should be conceptualised as a distinct political generation in the first place, and what is gained from doing so. Focussing on the case of Britain, this study explores the extent to which the Millennials are a distinct political generation in terms of political participation, political apathy, and political alienation, and considers how their conceptualisation as a distinct generation improves our understanding of their political characteristics. Furthermore, it tests the theory that their alienation from, rather than their apathy towards, formal politics can explain their distinct political behaviour. Through critiquing and developing conceptualisations of the Millennials as a political generation, and of political apathy, alienation and participation, this thesis challenges the conventional wisdom. The Millennials are a distinct generation in terms of their political participation, apathy and alienation – but they are distinct for their lack of participation, their unusually high levels of apathy towards formal politics, and their unusually low levels ofalienation from it. The Millennials have the potential to be the most politically apathetic, and least politically alienated, generation to have entered the British electorate since World War Two. In addition, this research also shows that while generational differences are significant and often substantial, they make only a limited contribution to explaining variation in political apathy, alienation and participation. This research argues, therefore, that future studies into and policy responses to the political behaviour of young people must recognise their distinct levels of political apathy. At the same time, however, the focus on political generations should not be so intense as to obscure the role of more influential causes of differences in political participation.